Women and Political Participation in Nigeria: A Critical Assessment and the Way Forward - SALAU, Jamiu Adewale; MAMUDU, Ganni Kashetu; VITOWANU, Gbetayi Jacob (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2024)
In line with National Centre for Women Development, Nigerian women constituted nearly half of the population of the country (49.31%). Nigeria had recorded low participation of women in politics, both in elective and appointive positions. In the history of Africa, particularly in Nigerian political trend, it was obvious that, the major roles performed by women in the society were domestic and supernatural affairs. The under representation of women in political participation in Nigeria had gained prominence from pre-colonial era till date. Recently, according to “National Centre for Women Development” on women’s participation in Nigerian politics, women’s involvement in active politics started gaining prominence from fourth republic. Over two decades, Nigeria had enjoyed uninterrupted democratic governance, which involved 6.7% of women participated in politics, which was below the global average of 22.5%. In the immediate past administration of President Muhammad Buhari, only seven (7) out of forty three (43) ministers in his executive cabinet were women representing 16.7%. In the ninth National Assembly, women have nineteen seats out of 469 members representing 10.9% in National Assembly (2019-2023). This paper was designed to critically assess the rate of women in political participation in Nigeria. The researcher recommended that, women should be encouraged to actively involve in political participation in their various societies by the people of their constituency. Federal Government through the National Assembly should continue to review the electoral act to give waivers to women candidacy by encouraging them to show more interest in politics through advocacy on gender equality.